Problems of working women as perceived by some Home Economics teachers in state colleges & universities - Viray, Firma C. (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2003)
The purpose of this study was to investigate the perceived socio cultural roles and problems affecting working women and their family. The respondents were 60 Home Economics (HE) teachers who attended the Annual Conference of Philippine Association for Home Economics in the State Colleges and Universities. Results showed that they still consider being a mother and wife as their traditional role, even when they are working outside the home while most of them are highly educated. Their perception on the problems of low pay, lower status, gender discrimination, sexual harassment, family relationship and home management differ. However, they identified home management as the number one problem because most of the burden of domestic work and the family needs were expected remain on their shoulders no matter what financial gains they can contribute to the family. There is a need to create programs on gender sensitivity to understand the plight of working women. This should be included in school curriculum to be taken by both male and female students. The importance of the role of women to the development of the family must be emphasized to both husband and wife for the need to work as partners in all aspect of their life. Inculcation of positive attitudes towards the significant role of working women should be selected as topics in training/seminars/conferences to advocate their plight. This is to make everyone understand the significant contribution of working women in the development of the family and the nation as a whole.